1994
DOI: 10.1007/bf02369744
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of a monosilane rf-discharge plasma

Abstract: A monosilane if-discharge plasma is investigated by numerical methods. The results of Monte Carlo calculations of the electron kinetics are compared with the results of calculations in the hydrodynamic approximation. It is shown that the hydrodynamic model works well over the entire range of parameters of a plasma-chemical reactor for the deposition of amorphous silicon films. Certain plasma parameters of importance from the standpoint of cooling, such as the dissociation frequency of monosilane and the energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 16 publications
2
29
0
Order By: Relevance
“…It simply reflects the very good agreement found for the isotropic distribution f 0 (z, U, t) ( Fig. 5), because both quantities are averages of it according to relations (7) and (8). The particle flux density (9) and energy flux density (10) are related to the anisotropic distribution f 1 (z, U, t).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…It simply reflects the very good agreement found for the isotropic distribution f 0 (z, U, t) ( Fig. 5), because both quantities are averages of it according to relations (7) and (8). The particle flux density (9) and energy flux density (10) are related to the anisotropic distribution f 1 (z, U, t).…”
Section: Resultssupporting
confidence: 66%
“…One of the approaches consists of the solution of the electron Boltzmann equation. So far, the treatment of this kinetic equation is widely restricted to timedependent, but spatially homogeneous plasmas [1][2][3][4][5][6] or to space-dependent, but stationary plasmas [7][8][9][10][11][12][13][14][15][16][17]. In recent years the spatiotemporal description of the kinetics of electrons in spatially one-dimensional plasmas [18][19][20] became possible, too.…”
Section: Introductionmentioning
confidence: 99%
“…In [31] no calculations were performed for Kr and Xe, but it was stated that the TNM effect should take place in these gases, too. Such calculations for Xe were carried out in [28,32], where the reduced electric field was switched from a relatively high (1-5 Td) to a low (0.01 Td) value. It was shown that during the EEDF relaxation there exists a time interval where the electron mobility is negative.…”
Section: Transient Negative Mobilitymentioning
confidence: 99%
“…It can be, for instance, accompanied by a double layer (internal sheath [20]). Electro-negative gas discharges are thus rather complex and the investigation of the spatio-temporal structure of the discharge as a function of external control parameters (current, voltage, frequency, pressure, and geometry) is a great theoretical [21,22,23,24] and experimental [25,26,27,28,29,30] challenge. In addition, electro-negative processing gases are reactive molecular gases, with internal degrees of freedom, which lead to a quite involved plasma chemistry.…”
Section: Introductionmentioning
confidence: 99%